Analysis of palm oil industry cluster in Jambi Province - Erfit Erfit (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2017)
This study aims to analyze palm oil industry clusters in Jambi Province. This study is a collective case study (survey and case study). The result shows that Jambi Province has a considerable potential for the development of palm oil industry. It can be seen from the development of plantation area, production of Palm Fresh Fruit Bunches, Crude Palm Oil, Palm Kernel Oil, and Palm Oil Mill. However, there are still very limited downstream products of palm oil that can be produced. Based on SWOT analysis, it shows that beside having large opportunities, Jambi Province also faces with various obstacles and threats on the way to develop palm oil industry. Keywords: Industry cluster, palm oil industry, SWOT analysis